Domain-based biophysical characterization of the structural and thermal stability of FliG, an essential rotor component of the Na(+)-driven flagellar motor - Onoue, Yasuhiro (Biophys Physicobiol, 2016)
Many bacteria move using their flagellar motor, which generates torque through the interaction between the stator and rotor. The most important component of the rotor for torque generation is FliG. FliG consists of three domains: FliG(N), FliG(M), and FliG(C). FliG(C) contains a site(s) that interacts with the stator. In this study, we examined the physical properties of three FliG constructs, FliG(Full), FliG(MC), and FliG(C), derived from sodium-driven polar flagella of marine Vibrio. Size exclusion chromatography revealed that FliG changes conformational states under two different pH conditions. Circular dichroism spectroscopy also revealed that the contents of α-helices in FliG slightly changed under these pH conditions. Furthermore, we examined the thermal stability of the FliG constructs using differential scanning calorimetry. Based on the results, we speculate that each domain of FliG denatures independently. This study provides basic information on the biophysical characteristics of FliG, a component of the flagellar motor.